Analysis of Bilingualism in the University Environment Challenges and Potentials - Afni, Eka Nur; Noviyanti, Fitri; Putri, Aisyah Nur Azizah (Universitas Teknokrat Indonesia, 2025)
This study examines the use of Javanese and Indonesian Bilingualism in the university environment. The research design employed a qualitative approach to gain in-depth insights into the phenomenon of Bilingualism. The participants included four fifth-semester students majoring in English Education, chosen for their bilingual experiences in using Javanese and Indonesian. Data were collected through in-depth interviews, participatory observations, and the analysis of social interactions in academic and informal contexts. The data analysis involved thematic analysis. The results show that Javanese strengthen social relations in informal contexts, while Indonesians dominate formal situations such as lectures. The main challenge is the adaptation of non-Javanese students to Javanese and the risk of marginalization of local languages. Bilingualism has great potential in strengthening cultural identity and flexibility of communication. Universities are expected to support the sustainability of local languages through inclusive programs such as the introduction of Javanese culture and language. This strategy is important for maintaining cultural diversity and improving students' language skills in academic and social settings.Keywords: Bilingualism, Javanese language, Indonesian language.